Nafertisite, Na3Fe2+ 10Ti2(Si6O17)2O2(OH)6F(H2O)2, from Mt. Kukisvumchorr, khibiny alkaline massif, kola peninsula, Russia: Refinement of the crystal structure and revision of the chemical formula - CAMARA ARTIGAS, Fernando; Sokolova E; Abdu Y; Hawthorne FC (European Journal of Mineralogy, 2014)
The crystal structure of nafertisite, Na3Fe102+Ti2(Si6O17)(2)O-2(OH)(6)F(H2O)(2), from Mt. Kulcisvumchorr, Khibiny alkaline massif, Kola peninsula, Russia, a 5.358(1), b 16.204(3), c 21.976(4) angstrom, beta 94.91(1)degrees, V 1901.0(7) angstrom(3), space group A2/m, Z = 2, D-calc. 3.116 g/cm(3), has been refined to an R-1 value of 5.60 % for 2747 observed [F-o > 4 sigma F] unique reflections collected with a single-crystal diffractometer. The crystal used in the collection of the X-ray intensity data was analyzed by electron microprobe; the Fe3+/(Fe2++Fe3+) ratio was measured by Mossbauer spectroscopy, and FTIR and Raman spectra were collected. The empirical formula was calculated on the basis of (O + F + OH + H2O) = 44.39 pfu: (Na1.39K0.61)(Sigma 2)Na-1(Rb0.06Cs0.02 square(0.921))(Sigma 1)(Fe9.112+Mg0.46Mn0.22Al0.10Na0.09Ca0.02)(Sigma 10)(Ti1.90Nb0.05Mg0.03Zr0.02)(Sigma 2)[(Si11.81Al0.19)(Sigma 12)O-34]O-2(OH)(6) (F0.86O0.14)(Sigma 1)(H2O)(1.39); Z = 2; the content of H2O was calculated from the structure-refinement results. The HOH layer is the main structural unit in nafertisite. It consists of a central octahedral (O) sheet and two adjacent heteropolyhedral (H) sheets. The O sheet is composed of Fe2+-dominant M(1-3) octahedra, the M(1-3) sites are fully occupied and the ideal composition of the O sheet is Fe-10(2+) apfu. The H sheet is composed of the nafertisite T6O17 ribbons and Ti-dominant D octahedra. The chemical composition of the nafertisite ribbon is (Si11.81Al0.19)O-34 apfu, ideally (Si6O17)(2)pfu. In the crystal structure of nafertisite, HOH layers alternate with intermediate (I) blocks along c. In the I block, the A, B, C and W sites are occupied by (Na1.39K0.61), Na, (square 0.92Rb0.06Cs0.02) and [(H2O)(1.39)square(0.61)] Pfu, respectively. The chemical composition of the I block of the general formula A(2)BCW is [(Na-1.39 K-0.61)Na-1(square 0.92Rb0.06Cs0.02(H2O)(1.39)] pfu, ideally Na-3(H2O)(2) pfu. Nafertisite is closely related to the astrophyllite-group minerals.